2006
DOI: 10.1177/1359105306069091
|View full text |Cite
|
Sign up to set email alerts
|

Examining Exercise Dependence Symptomatology from a Self-determination Perspective

Abstract: Background Pulling from Self-Determination Theory (SDT; Deci & Ryan, 1985), this study examined whether individuals classified as ‘nondependent-symptomatic’ and ‘nondependent-asymptomatic’ for exercise dependence differed in terms of reported levels of exercise-related psychological need satisfaction, self-determined versus controlling motivation and exercise behavior. In addition, we examined the type of motivational regulations predicting exercise behavior among these different groups, and their role as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 38 publications
8
48
1
3
Order By: Relevance
“…These indicated appropriate internal consistency for the measures of obsessive passion, relatedness, and dance dependence. The alpha coefficients for autonomy and competence were slightly low but in line with previous reports (e.g., Edmunds et al, 2006); however, harmonious passion demonstrated a concerning level of reliability. Factor analysis indicated two low loading items (10 and 6); removal of these marginally improved model fit and reliability (α = .66) however given the lack of substantial improvement the full item set validated in previous studies was retained.…”
Section: Scale Reliabilitysupporting
confidence: 91%
“…These indicated appropriate internal consistency for the measures of obsessive passion, relatedness, and dance dependence. The alpha coefficients for autonomy and competence were slightly low but in line with previous reports (e.g., Edmunds et al, 2006); however, harmonious passion demonstrated a concerning level of reliability. Factor analysis indicated two low loading items (10 and 6); removal of these marginally improved model fit and reliability (α = .66) however given the lack of substantial improvement the full item set validated in previous studies was retained.…”
Section: Scale Reliabilitysupporting
confidence: 91%
“…The latter is consistent with most of the literature which shows introjection to be more highly correlated with identified regulation than with external regulation in other behavioural domains (c.f., (Chemolli & Gagne, 2014) and with previous research using the BREQ-2. (e.g., Edmunds et al, 2006a;Markland, 2009;Markland & Tobin, 2004;Markland & Tobin, 2010;. Taken together, these findings are broadly in harmony with previous studies and support Chemolli and Gagné's contention that evidence for a continuum conception of self-determination is weak and inconsistent with the broader tenets of SDT.…”
Section: Relationships Among Brwq Subscalessupporting
confidence: 79%
“…Researchers have undertaken limited walking specific studies to examine behavioural regulations; however other studies have shown that the hypothesized relationships between behavioural regulations and physical activity are evident for structured and strenuous exercise, but not for lifestyle physical activity behaviours (e.g., walking instead of taking motorized transport, easy walking) or mild exercise in the same sample (Edmunds, Ntoumanis, & Duda, 2006a, 2006bSilva et al, 2010;Vlachopoulos, Ntoumanis, & Smith, 2010). As suggested by Silva et al it is possible that engaging in lifestyle behaviours may require less cognitive effort and therefore be regulated by more automatic and habitual processes (Silva et al, 2010).…”
Section: Self-determination Theorymentioning
confidence: 99%
“…An alternative perspective relating to the positive associations between body-related guilt and introjected and identified regulations is that guilt may foster maladaptive forms of physical activity. Previous research investigating the motivating forces behind maladaptive forms of exercise such as dependence, has reported introjection as the strongest predictor of maladaptive activity (Edmunds, Ntoumanis, & Duda, 2006). This is the first study to extend self-objectification framework to examine the relations among body-related guilt, physical activity motivation, and behavior.…”
Section: Discussionmentioning
confidence: 93%